The RING finger protein Siah-1 regulates the level of the transcriptional coactivator OBF-1 - Tiedt, Ralph (Oxford University Press, 2001)
The transcriptional coactivator OBF-1, which interacts with Oct-1 and Oct-2 and the octamer site DNA, has been shown to be critical for development of a normal immune response and the formation of germinal centers in secondary lymphoid organs. Here we have identified the RING finger protein Siah-1 as a protein interacting specifically with OBF-1. This interaction is mediated by the C-terminal part of Siah-1 and by residues in the N-terminus of OBF-1, partly distinct from the residues required for formation of a complex with the Oct POU domains and the DNA. Interaction between Siah-1 and OBF-1 leads to downregulation of OBF-1 protein level but not mRNA, and to a corresponding reduction in octamer site-dependent transcription activation. Inhibition of the ubiquitin-proteasome pathway in B cells leads to elevated levels of OBF-1 protein. Furthermore, in immunized mice, OBF-1 protein amounts are dramatically increased in primary activated B cells, without concomitant increase in OBF-1 mRNA. These data suggest that Siah-1 is part of a novel regulatory loop controlling the level of OBF-1 protein in B cells.